History of traumatic brain injury in individuals committing sexual offenses - Agrawal, Amit; Singh, Vijender; Maurya, Ved Prakash; Mishra, Rakesh (Nepal Journal of Neuroscience, 2024)
Recent research in patients with traumatic brain injuries (TBIs) focus on several challenges addressing the spectrum of challenges in children, adolescents and in adults. These changes include social, behavioural, cognitive, academic, and psychosocial complications severity varying across the spectrum of TBIs (from mild to severe).